Integration of Gender Equality Values Through Innovative Development of Interactive E-Modules in Social Studies Subject - Utama, Taqwa Ridlo; Suyahmo, Suyahmo; Purnomo, Arif (JESS (Journal of Educational Social Studies), 2023)
Amidst the necessity for inclusive educational materials, this study endeavors to develop an E-Module that seamlessly integrates Gender Equality Values into the junior high school Social Studies curriculum.. The research product is an electronic module built using software and undergoes evaluation by experts, alongside feedback from teachers and students. Employing a Research and Development (R&D) approach, following the ADDIE model, the e-learning module undergoes a validation process. This validation process involves two subject matter experts: one specializing in gender studies and another in history, along with a media expert and a Social Studies teacher. The results of the validation indicate the high validity of the Interactive E-Module, with all involved parties providing strong validation scores. On average, expert and teacher assessments resulted in a validity score of 94.7%. Each party consistently achieved an average of 90% for both content and E-Module design. These results underscore the e-learning module's suitability for use, making it a highly recommended resource for Social Studies teachers at the junior high school level.